Recognition of Normal Fetal Cardiac Structures - Uzun, Orhan; Balcı, Burçin Karamustafaoğlu; Goynumer, Gokhan (Journal of Fetal Medicine, 2016)
Fetal heart examination requires in depth knowledge of fetal cardiac physiology and fetal cardiac anatomy. Therefore, the cardiac sonographer must possess considerable skills to acquire optimum images on cardiac anatomy on predefined standard views. An appropriate interpretation of acquired fetal cardiac images is also a basic requirement that is expected from a cardiac sonographer. Any cardiac ultrasound operator who performs the fetal heart scan is expected to recognize normal cardiac structures, to assess myocardial function and heart rhythm but also should be able to pick up any deviation from well-defined normality.
Keywords: Fetus; Heart; Anomaly; Three-vessel trachea; Four chamber; Cardiac outflow tract